Inovasi Metode Pembelajaran Pendidikan Agama Islam (PAI) di Era Digital dalam Penguatan Moderasi Beragama - Masyitah Masyitah (LaKaspia, 2025)
The development of digital technology has brought significant changes to the world of education, including Islamic Religious Education (IRE). The challenges of the digital era are not only related to learning methods and media, but also to strengthening the values of religious moderation among students. This article aims to examine innovations in IRE learning methods in the digital era and their role in instilling the values of religious moderation. The method used is a literature study by analyzing various literature, scientific journals, and relevant sources related to PAI learning, digital technology, and religious moderation. The results of the study show that innovations in digital-based learning methods, such as e-learning, blended learning, and the use of educational social media, can increase the effectiveness of PAI learning while strengthening tolerant, inclusive, and moderate attitudes among students. Thus, PAI learning innovation in the digital era has a strategic role in shaping a religious, critical, and moderate generation